S5 Prevalence Of Ige Sensitisation To 'improver Mix' Enzymes Among Symptomatic Bakers Working In Uk Scratch Bakeries. (10th November 2014) - Jones, M; Welch, J; Turvey, J; Cannon, J; Fitzgerald, B; Szram, J; Cullinan, P
Abstract : Introduction and objectives: Bakers working in supermarket scratch bakeries in the UK are exposed not only to flour and fungal alpha amylase but also other enzymes, incorporated in a pre-mixed bag of 'dough improvers'. Bakers and their employers are usually unaware of which enzymes are being used within the 'improver mix'. We have examined the question of whether supermarket bakers develop sensitisation to 'improver mix' enzymes other than fungal alpha amylase. Methods: We assayed specific IgE sensitisation in 300 bakers employed by one of two large UK supermarkets who, at routine health surveillance, had declared work related upper or lower respiratory symptoms. Sensitisation was determined using radioallergosorbent assay to enzymes contained within the specific 'improver' mix used by the employing supermarket; each mix contained eight individual enzymes which were not necessarily common to both supermarkets. Results: Bakers were sensitised to each of the individual 'improver' enzymes with a prevalence ranging from 1.8% to 23.9%; the frequency did not appear to be associated with the quantity of enzyme incorporated in the mix. Sensitisation was far more likely if a baker was sensitised also to either flour or fungal alpha amylase; but a small proportion (5%) of bakers who were sensitised to neither flour nor fungal alpha amylase had specific IgE to one or more of the 'improver mix' enzymes. Conclusions: Bakers working in UK supermarket bakeries can become sensitised to improver enzymes other than fungal alpha amylase. The clinical significance of this remains unclear but the message is important both in the diagnosis of bakers with work-related respiratory symptoms and in any programme of immunological surveillance.